Student’s reflective thinking (An analysis of student’s reflective journal in English paragraph writing) - Dina Rachmawati; Audrey Akbaria Adinda Putri; Murti Ayu Wijayanti (Journal of Linguistics, Literacy, and Pedagogy, 2023)
This study outlines a content analysis that focused on students' level of reflective thinking, how much it contributed to the level of their writing and how they felt about using reflective journals. 15 students from the 2019/2020 Paragraph-based Writing course participated in this study, which was performed at the English Education Department of a state University located in Banten province. Students' writing samples and reflective journals were gathered through documentation, and responses to a questionnaire were gathered from them. The theme analysis technique, Oshima and Hogue's (2006) theory of paragraph writing, and Hatton and Smith's (1995) theory of reflective thinking level were all applied in this study. Three conclusions came from the data analysis. First, most of the students' reflective thinking skills fell under Descriptive Writing and First, the proportion of students' reflective thinking was identified between the levels of descriptive writing and descriptive reflection. Second, the analysis demonstrated that a rise in the number of cases at the Descriptive Reflection level was consistent with an improvement in the quality of students' writing. Meanwhile, the rise in the number of descriptive writing level incidents coincided with a decline in the level of students' writing. Third, despite being viewed as demanding and stressful, the usage of reflective journal in the class was viewed favorably because it helped students remember lessons and recognize their errors, which helped them to produce well-organized paragraphs. The results suggested that reflective journaling helped students to enhance their writing skills and may be used as a substitute for developing other language skills.